A study on Iraqi images in Malaysia mainstream English language newspapers - Kassed, Hanaa Kadum (2015)
Media and image have become important research areas in international relations and media studies. The occupation of Iraq by the United States has created many images of Iraq among other countries. Although there has been quite an extensive research on Iraq, especially during the period of occupation, reviews of literature reveal that there are still certain gaps on understanding its image from the Eastern media perspective. Thus, the main purpose of the study is to investigate the image of Iraq through the publication of news stories and articles in Malaysia that is considered as Islamic country with multiethnic community. The study also aims to reveal the image of Iraq by focusing on two Malaysian English newspapers - the New Straits Times press (NSTP) and the Star by applying both Framing Theory and Agenda Setting Theory. This study examines a longitudinal content analysis of 535 articles and news stories through three periods (before, during and after the occupation of Iraq). Descriptive statistics, Crosstab, Binomial test, Chi-square and Cramer‟s V are used to analyze the data. The result of this study shows that NSTP gave more emphasis to the issue of the policy of unipolar for the United States and framed it to focus on responsibility and reflected a neutral image of Iraq, while the Star gave more emphasis to the issue of Iraqi suffering and framed it through human interest with a negative image. Furthermore, the agenda setting issues in the NSTP has a bigger association on the image of Iraq while the Star proves the framing categories have a bigger association on the image of Iraq. Thus, this study can shed some light on how Eastern country views Iraq and this perhaps could help Iraq reform its image by expanding the scope of diplomatic, business and cultural actions. This study provides support to the theoretical proposition that the media are not successful in telling the audience what to think, but it is stunningly successful in telling the audience what to think about (first level of Agenda Setting). This study also provides support to the theoretical proposition that differences in media organizations have profound impact on how the important issues are framed